2016
DOI: 10.1002/prca.201500016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential breast cancer markers in nipple discharge by protein profile analysis using two-dimensional nano-liquid chromatography/nanoelectrospray ionization-mass spectrometry

Abstract: These tendencies in protein expression and markers provide new ways to identify breast cancer patients. Therefore, RP/RP 2D LC/MS/MS analyses of ND and the above three markers are supported as a new breast cancer diagnostic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…have found that CA2 and CA12 have prognostic power in colorectal carcinomas35; and Kurono et al . have reported that CA2 expression in breast cancer is significantly higher than normal tissues36. It is known that solid tumors are featured by the tumor microenvironment, with aberrant activation of numerous immune cells28.…”
Section: Discussionmentioning
confidence: 99%
“…have found that CA2 and CA12 have prognostic power in colorectal carcinomas35; and Kurono et al . have reported that CA2 expression in breast cancer is significantly higher than normal tissues36. It is known that solid tumors are featured by the tumor microenvironment, with aberrant activation of numerous immune cells28.…”
Section: Discussionmentioning
confidence: 99%
“…A number of strategies to determine the NAF proteome coverage have been undertaken many of which have been summarized by Pavlou et al, as part of a comparison with their own dataset of 854 proteins [20]. More recently, similar studies by Brunoro et al [21] and Kurono et al [22] identified 557 and 372 proteins, respectively. Mostly these studies have focused on optimizing protein and peptide separation using single breast samples from each patient.…”
Section: Clinical Relevancementioning
confidence: 99%
“…21 and Kurono et al. 22 identified 557 and 372 proteins, respectively. Mostly these studies have focused on optimizing protein and peptide separation using single breast samples from each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody columns may be used to deplete high-abundance plasma proteins from urine samples to allow for the detection of lower abundance proteins (8)(9)(10)(11)(12)(13)(14). Two-dimensional liquid chromatography (2D-LC) separation decreases sample complexity by using two columns prior to tandem mass spectrometry (MS/MS) and exhibits increased power in detecting low-abundance proteins (15,16). A method that combines antibody depletion with 2D-LC-MS/MS may facilitate the identification of biomarkers (17), although such a method has not previously been used to analyze nephrotic syndrome urine samples.…”
Section: Introductionmentioning
confidence: 99%